2020
DOI: 10.1016/j.neuroimage.2020.117211
|View full text |Cite
|
Sign up to set email alerts
|

Does hippocampal volume explain performance differences on hippocampal-dependant tasks?

Abstract: Highlights Evidence is mixed about whether hippocampal volume affects cognitive task performance. This is particularly the case concerning individual differences in healthy people. We collected structural MRI data from 217 healthy people. They also had widely-varying performance on cognitive tasks linked to the hippocampus. In-depth analyses showed little evidence hippocampal volume affected task performance.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 95 publications
4
39
3
Order By: Relevance
“…By contrast, in real-world contexts, the hippocampus is involved in the retrieval of multi-faceted, multi-modal autobiographical memories of our personal past experiences (Steinvorth, Levine, & Corkin, 2005). However, even when autobiographical memory recall was examined in a wide-ranging analysis of healthy people, Clark, Monk, Hotchin, et al (2020) did not find any significant relationship between overall hippocampal volume and recall of internal (episodic) details, a widely-used measure from the Autobiographical Interview (Levine, Svoboda, Hay, Winocur, & Moscovitch, 2002). To the best of our knowledge, only one study has examined the links between hippocampal subregion volumes and autobiographical memory recall in healthy individuals, reporting a positive association between the number of internal details on the Autobiographical Interview (Levine et al, 2002) and the volume of both the left subiculum and the combined left dentate gyrus (DG)/CA2/ CA3 region (Palombo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, in real-world contexts, the hippocampus is involved in the retrieval of multi-faceted, multi-modal autobiographical memories of our personal past experiences (Steinvorth, Levine, & Corkin, 2005). However, even when autobiographical memory recall was examined in a wide-ranging analysis of healthy people, Clark, Monk, Hotchin, et al (2020) did not find any significant relationship between overall hippocampal volume and recall of internal (episodic) details, a widely-used measure from the Autobiographical Interview (Levine, Svoboda, Hay, Winocur, & Moscovitch, 2002). To the best of our knowledge, only one study has examined the links between hippocampal subregion volumes and autobiographical memory recall in healthy individuals, reporting a positive association between the number of internal details on the Autobiographical Interview (Levine et al, 2002) and the volume of both the left subiculum and the combined left dentate gyrus (DG)/CA2/ CA3 region (Palombo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Extant studies have predominantly examined this relationship in terms of hippocampal grey matter volume. However, in reviewing the literature, Clark et al (2020) found mixed evidence for an association between hippocampal grey matter volume and performance on tasks assessing these cognitive functions in healthy individuals. They then proceeded to examine this issue in-depth by collecting data from a large sample of 217 young, healthy, adult participants but found little evidence that hippocampal grey matter volume was related to task performance ( Clark et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…We used the large data set (n = 217) from Clark et al’s (2020) study that comprised an MPM quantitative imaging protocol ( Callaghan et al, 2015 , 2019 ; Weiskopf et al, 2013 ), and cognitive task performance with wide variability in scores. While aspects of these data (hippocampal grey matter volume, cognitive task performance) have been reported before ( Clark et al, 2019 , 2020 ; Clark and Maguire, 2020 ), the tissue microstructure MRI data, measuring myelination and iron content, have not been published previously. The mixed literature relating to hippocampal grey matter volume and the dearth of studies investigating hippocampal grey matter myelination and iron content made the formulation of clear hypotheses difficult.…”
Section: Introductionmentioning
confidence: 99%
“…These include a poor theoretical conceptualization of why growth should be important to gaining a multifaceted skill such as navigation and mechanistically what is changing with hippocampal growth? These also include empirical considerations regarding sample size: other than Poppenk and Moscovitch (2011), who correlated recollection measures with hippocampal volume across multiple studies, the remaining studies were all significantly underpowered for correlation analyses compared to the preregistered experiments investigating structure-function associations (Clark et al, 2020;Hao et al, 2016;Weisberg et al, 2019). Additional issues we explore here with regard to the specialization argument are why one specific cognitive process should correlate specifically with hippocampal growth, why different behavioral studies appear to suggest variable dependent measures correlate with hippocampal growth, and how one should interpret an anterior/posterior hippocampal shift in volume.…”
Section: Weaknesses Of the Specialization Argument: Theoretical And Ementioning
confidence: 99%
“…Using sample sizes of from 80-100 healthy young volunteers, two studies showed no significant relationship between hippocampal volume and navigational ability, although such participants do vary quite widely in navigation ability (Hao et al, 2016;Weisberg et al, 2019). A third study, using 217 healthy young adults, found no associations between hippocampal volume and a range of tasks, including scene imagination and tasks related to spatial navigation (Clark et al, 2020). In the study by Weisberg and colleagues, participants navigated a large-scale virtual environment and pointed to locations and drew maps of the cities they had explored.…”
Section: Hippocampal Growth and Navigation: An Introduction To An Infmentioning
confidence: 97%